The fortification system of Medieval Philippopolis - Kamen Stanev (Приноси към българската археология, 2022)
Medieval Philippopolis (present-day Plovdiv) inherited the fortification system constructed in the 1st – 6th c. It consists of three “belts”. There are no data about changes up to the 12th c., with the exception of a ditch which protected the populated territories north of the fortress wall but has not yet been registered archaeologically. At the end of the 12th – beginning of the 13th c., there are data concerning several additions and later instances of destruction. Traces of those can be found at several places along the wall enclosing the high part of the Three Hills (Trimontium). It was at this time that significant changes took place – the vast area in the plain was abandoned, and a citadel was set up in the northern part of the Three Hills, in which a capacious water reservoir was built. At a later time, in the 13th – 14th c., a second wall was built, which fenced off the furthest northern part of the citadel. The latest information about the use of the Philippopolis fortificationsis from 1410, and after their being badly damaged in the wars between the sons of the Ottoman sultan Bayezid I, their maintenance was abandoned.